Policultivo de machos de tilápia do congo, Tilapia rendalli Boulenger, 1912, com carpa espelho, Cyprinus carpio L., 1758 vr. specularis Policultive of male congo tilapia, Tilapia rendalli Boulenger, 1912, and mirror carp, Cyprinus carpio L., 1758 vr. sp (Revista Ciência Agronômica, 2023)
RCA